Sustainable Development Report 2020 The Sustainable Development Goals and Covid-19 Includes the SDG Index and Dashboards - Sachs, Jeffrey (Social Sciences, 2021)
The Sustainable Development Report 2020 features the SDG Index and Dashboards, the first and widely used tool to assess country performance on the UN Agenda 2030 and the Sustainable Development Goals. It contains insights on sustainable development and the impact of COVID-19 on the SDGs. This title is available as Open Access on Cambridge Core.